Enhancing Students’ Nature of Science Using STEM Engineering Design Process in Elements, Compounds, and Mixtures Topic - Fitriyyatul Muslihah; Nanang Winarno; Andini Fajarwati; Sujito Sujito (Didaktika: Jurnal Kependidikan, 2024)
A scientifically educated culture is the ultimate goal of science education worldwide, and one of the key elements in acquiring scientific literacy is comprehending the nature of science (NOS). This study aimed to enhance the views of Junior High School students of nature of science (NOS) in Elements, Compounds, and Mixtures Topic using the STEM engineering design process. The method applied in this research is quasi-experiment. The sampling technique used was convenience sampling, which was taken from grade 9 in one of the junior high schools in Bandung, Jawa Barat, Indonesia, with the age range 14-15 years old. The sample consisted of 38 students in total, consisting of the experimental class (n=19 students) and control class (n=19 students). The experimental class is taught using the STEM engineering design process, while the control class is conducted using conventional learning. The result of this research was that the N-gain students’ Nature of Science of experiment class shows the number of 0.4051, which is categorized as moderate improvement, whereas the control class shows the number of 0.0151, which is categorized as low improvement. The hypothesis test using an independent sample t-test for Nature of science shows that there is a difference between the experimental class and control class, where the experimental class gain higher achievement. Based on this research, the STEM engineering design process could be considered to an alternative to improve students’ nature of science.